The Prothrombin Time in the Newborn: Effect of Contact Activation - Shanberge, J. N; Matsuoka, T (Thrombosis and Haemostasis, 1967)
The effect of foreign-surface contact on prothrombin conversion in adult plasma is compared to that of the newborn. The tests utilized in this comparison were the one-stage prothrombin time of Quick, the second stage of the thromboplastin generation test, and the prothrombin consumption test or the serum prothrombin time. In all of these there is much less acceleration produced by foreign-surface contact in the plasma of the newborn. Acceleration of the prothrombin conversion time is directly related to an increase in activity of factors VII and XL At no time could an increase in prothrombin activity be demonstrated. The decreased acceleration produced by foreign-surface contact in the plasma of the newborn is due primarily to a decreased level of factor VII as well as those factors necessary for its activation.